Movilidad peatonal y capacidad de acogida del espacio público en el contexto comercial y de servicios, La Alborada – Guayaquil. - María Lorena Sánchez Padilla; Carlos Suco; Laura Campoverde; Ricardo Valencia (NOVASINERGIA)
Urban resources such as equipment, services, and touristic sites are attracting nuclei of people. In the urban structure, the modes of mobility a location possesses give it a determining role complemented by accessibility and connectivity whose effectiveness is measurable on a smaller territorial scale, such as a sector or a neighborhood. The adverse effects of the SARS-2 COVID-19 pandemic generatedthe tendency to isolate neighborhoods, such as the case of La Alborada in Guayaquil, with most of its pedestrian accesses blocked, a reality that differs since it is the sector with the most remarkable economic dynamism. This study aims to quantify the variables of pedestrian mobility and the capacity to accommodate people on the central commercial axis using official maps, measurements, and direct observation data collected in public spaces. The results reflect that the linear commercial corridor is segmented into five sections. In the initial and final sections (1, 2, and 5), accessibility is deficient. The intermediate ones (3 and 4) have accessible sidewalks, trees on the sidewalks, and street medians because of public interventions; the deficit indicators are the absence of benches for rest; visual permeability is mild on the ground floor because of non-scenic spaces such as parking lots.